Axonopathy is a compounding factor in the pathogenesis of Krabbe disease - Castelvetri, Ludovico Cantuti (2011)
Loss-of-function of the lysosomal enzyme galactosyl-ceramidase (GALC) causes the accumulation of the lipid raft-associated sphingolipid psychosine, the disruption of postnatal myelination, neurodegeneration and early death in most cases of infantile Krabbe disease. This work presents a first study towards understanding the progression of axonal defects in this disease using the Twitcher mutant mouse. Axonal swellings were detected in axons within the mutant spinal cord as early as one week after birth. As the disease progressed, more axonopathic profiles were found in other regions of the nervous system, including peripheral nerves and various brain areas. Isolated mutant neurons recapitulated axonal and neuronal defects in the absence of mutant myelinating glia, suggesting an autonomous neuronal defect. Psychosine was sufficient to induce axonal defects and cell death in cultures of acutely isolated neurons. Interestigly, axonopathy in young Twitcher mice occured in the absence of demyelination and of neuronal apoptosis. Neuronal damage occurred at later stages, when mutant mice were moribund and demyelinated. Altogether, these findings suggest a progressive dying-back neuronal dysfunction in Twitcher mutants.